The Effect of High Intensity Interval Training (HIIT) on Improving The Anaerobic Endurance of Basketball - Windo Wiria Dinata; Mustika Fitri; Amelia Putri Rahmadani (Faculty of Sport and Health Sciences, 2025)
Basketball performance depends on strong anaerobic endurance due to repeated high-intensity movements such as sprinting, jumping, and rapid directional changes. High-Intensity Interval Training (HIIT) is widely recognized as an effective method to improve anaerobic capacity because it reflects the intermittent demands of basketball and enhances metabolic efficiency. This study aimed to examine the effect of HIIT on the anaerobic endurance of basketball players at the Halilintar Bukittinggi Club. This experimental study used a one-group pre-test and post-test design. The participants were 12 basketball players aged 15–18 years selected through purposive sampling. The intervention consisted of a 6-week HIIT program conducted three times per week. Anaerobic endurance was measured using the Running-Based Anaerobic Sprint Test (RAST), with fatigue index as the main indicator. Data were analyzed using a paired sample t-test. The results showed a notable improvement in anaerobic endurance. The average fatigue index decreased from 10.11 to 6.07, indicating an improvement with Cohen’s d was 0.90. Since a lower fatigue index reflects better anaerobic endurance, this result demonstrates a meaningful performance enhancement. Statistical analysis confirmed a significant effect (t = 8.24; p < 0.05). In conclusion, HIIT is an effective training method for improving anaerobic endurance in young basketball players.